(untitled) (Research, Society and Development, 2023)
Hands are the main route of microorganisms’s transmission. Hand hygiene with the use of alcohol gel reservoirs requires physical contact between the hands and the triggering device, usually a button or lever, to release a small amount of alcohol gel. If any user of this device does not correctly use and wash their hands, microorganisms can be deposited on the button that activates the alcohol gel reservoir, which may lead to contaminants on the hands of other users of the device. The objective of this work was to develop a reservoir (dispenser) of alcohol gel for hands that does not require physical contact for activation (automatic), with the aim of investigating whether physical contact (or its absence) can interfere with microbial counts. The construction of the device proved to be feasible. There was a reduction in the bacterial load (colony forming units) in the automated device compared to the non-automated one.